Microfluidic protein crystallisation controlled using spontaneous emulsification1. Issue 17 (7th September 2015) - Fukuyama, Mao; Akiyama, Aoi; Harada, Makoto; Okada, Tetsuo; Hibara, Akihide
<x xml:space="preserve">Abstract</x> Microdroplet-based protein crystallisation using spontaneous emulsification is proposed and demonstrated. The dependency of crystal number in a single microdroplet on the surfactant concentration is discussed.